2014
DOI: 10.1902/jop.2014.130559
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy During Supportive Periodontal Care: Clinical, Microbiologic, Immunoinflammatory, and Patient‐Centered Performance in a Split‐Mouth Randomized Clinical Trial

Abstract: PDT as an exclusive therapy may be considered a non-invasive alternative for treating residual pockets, offering advantages in the modulation of cytokines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
3
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(131 citation statements)
references
References 48 publications
3
116
3
9
Order By: Relevance
“…Among these studies, only four reported the microbiological outcomes by numeric results on tables. 25,26,27,28 Real-time PCR: Kolbe et al 27 showed a non-significant trend to decrease the quantities (amounts: log 10 ± SEM) of P. gingivalis (1.6 ± 1.4 to 1.0 ± 1.4) and T. forsythia (4.9 ± 3.6 to 4.7 ± 3.8) from PMP baseline to 6 months, respectively, and stability for A. actinomycetemcomitans (2.7 ± 3.1 to 2.7 ± 2.5). There were no differences over time in the percentage of sites harboring T. forsythia and A. actinomycetemcomitans, whereas a significant decrease in the frequency of P. gingivalis was observed.…”
Section: Spg + Sbg Resultsmentioning
confidence: 99%
“…Among these studies, only four reported the microbiological outcomes by numeric results on tables. 25,26,27,28 Real-time PCR: Kolbe et al 27 showed a non-significant trend to decrease the quantities (amounts: log 10 ± SEM) of P. gingivalis (1.6 ± 1.4 to 1.0 ± 1.4) and T. forsythia (4.9 ± 3.6 to 4.7 ± 3.8) from PMP baseline to 6 months, respectively, and stability for A. actinomycetemcomitans (2.7 ± 3.1 to 2.7 ± 2.5). There were no differences over time in the percentage of sites harboring T. forsythia and A. actinomycetemcomitans, whereas a significant decrease in the frequency of P. gingivalis was observed.…”
Section: Spg + Sbg Resultsmentioning
confidence: 99%
“…[49][50][51] Three out of the 8 studies have also evaluated the changes in terms of inflammatory markers. 47,50,52 Two studies have revealed statistically significantly higher reductions in the investigated inflammatory markers following the use of PDT, 47,50 while one study detected no differences 52 (Table 3). …”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 97%
“…44,45 An additional improvement for the reduction of BOP was reported in 5 out of the 8 studies. [44][45][46][47][48] While three studies have found a statistically significant effect of the additional use of PDT on the reduction of periodontal pathogens, [46][47][48] three other studies have failed to reveal statistically significant differences between the treatment groups. [49][50][51] Three out of the 8 studies have also evaluated the changes in terms of inflammatory markers.…”
Section: Use Of Pdt As Adjunct To Nonsurgical Periodontal Therapy In mentioning
confidence: 99%
“…Kolbe et al 33) 2014 CP (22) residual pockets during SPT split-mouth a-PDT (22) Diode laser (660 nm, 60 mW) + MB (10 mg/ml), 1 min 6 months • There was no significant difference in improvement of PD and CAL among three group.…”
Section: Srp (30) Srp (H)mentioning
confidence: 97%